The Effects of Climatic Variations on Peat Swamp Forest Condition and Peat Combustibility - Lailan, Syaufina (2002)
A study on the effects of climatic variations on peat swamp forest condition and peat combustibility was conducted in peat swamp forest of Sungai Karang Forest Reserve, Tanjong Karang, Selangor, Malaysia. The objectives of the study were to determine: 1). Climatic variations in the study area, 2). The effects of climatic variations on peat swamp forest condition; 3). Peat com bustibility and its influencing factors, and 4). The effects of forest fire on peat swamp forest condition. The study was conducted in compartment 127 during two periods, namely: October 1999 to January 2000 and May 2000 to October 2000, while, the study on forest fire effects was conducted in compartment 132 from October 1999 to January 2000. Climatic water balance, drought occurrences analysis and drought index using Keetch- Byram Drought Index (KBDI) were used to describe clim atic variations. Investigation on peat swamp forest condition included peat characteristics such as moisture content, pH, organic content, ash content. calcium, potassium, magnesium, sodium and water level. Heat content and combustion rate were measured to determine peat combustibility. All data obtained were analysed statistically by using multivariate cluster analysis, univariate and multiple regression. The study defined dry season and wet season as a period when monthly rainfall is similar or less than 125 mm and m ore than 125 mm respectively. The area has two drought periods, namely: January, February, and March as the first period and May to August as the second period. Statistically, the season affected moisture content, bulk density, potassium, magnesium, sodium and water level. By using weekly rainfall prediction, the critical peat moisture content to fire is 355%. The high stages of KBDI in 1999/2000 were observed twice, namely on 25 and 26 April 2000. KBDI can be used in predicting moisture content and water level in the study area. Based on the area burned, burning depth and ash color, forest fire occurred on 9 August 1999 was a light intensity fire. The fire, however, caused the decreasing of hydraulic conductivity and magnesium and the increasing of potassium and sodium.